Experience of Earth. The Case of Janina Degutytė - Šmitienė, Giedrė (Tautosakos darbai, 2017)
The article presents a description of the peculiar experience of earth based on letters written by poet Janina Degutytė in 1972–1989. The city-born poet happens to find herself at a homestead, the original center of agriculture, and recognizes this place as an especially suitable one for her to live – she feels comfortable and peaceful there. Besides, her sick and physically fragile body confirms suitability of this place, feeling revived even in medical terms. Life in the countryside means both living on the ground and in the air. The article describes the integral feeling of earth and sky. The earth is experienced in several ways: by walking on it, by planting and growing, and by eating food received from it. All these ways shape and reshape the human body, senses and knowledge. All these ways also reveal support of the ground, and depict subjective trust in it.This closely surveyed case of the ground’s attraction experienced by Degutytė leads to another view of the boom in collective gardening of the 1960s and 1970s in the Soviet Lithuania. As well as mass purchasing of summerhouses in the countryside several decades later, the collective gardening could have been supported by the latent longing for the ground and farming activities. The author of the article examines such spontaneous experience of the ground as continuation of the agricultural tradition.The concept of tradition is reviewed in several aspects. The author raises a question whether or not direct inheritance is the only way of continuing the tradition. It is supposed that tradition, at least partly, survives in the environment and can manifest itself as an attraction of suitable places and activities. Stepping back from the concept of tradition represented by collections of things, the author of the article proposes the concept of lived tradition based on corporal perception and sensual experience.
Keywords: -